UNSTEADY VIBRATIONS OF PLANE MULTILAYERED PIEZOELEMENT IN VIEW OF ELASTIC REINFORCING LAYER AND AN ACOUSTIC MEDIUM - Grigoryeva, L. O. (Computer Science and Applied Mathematics, 2017)
Numerical study of unsteady stress-stain state of multilayered planar electromechanical transformers with elektroded coupling surfaces at electrical disturbances are developed. A study of electromechanical transducer state options dynamics depending on the number of elektroded layers with the same polarization direction and impact of elastic layer and the acoustic environment assessment is provided.